Changes in Bacterial Community Composition and Dynamics and Viral Mortality Rates Associated with Enhanced Flagellate Grazing in a Mesoeutrophic Reservoir - Šimek, Karel (American Society for Microbiology, 2001)
Bacterioplankton from a meso-eutrophic dam reservoir was size fractionated to reduce (<0.8-μm treatment) or enhance (<5-μm treatment) protistan grazing and then incubated in situ for 96 h in dialysis bags. Time course samples were taken from the bags and the reservoir to estimate bacterial abundance, mean cell volume, production, protistan grazing, viral abundance, and frequency of visibly infected cells. Shifts in bacterial community composition (BCC) were examined by denaturing gradient gel electrophoresis (DGGE), cloning and sequencing of 16S rDNA genes from the different treatments, and fluorescence in situ hybridization (FISH) with previously employed and newly designed oligonucleotide probes. Changes in bacterioplankton characteristics were clearly linked to changes in mortality rates. In the reservoir, where bacterial production about equaled protist grazing and viral mortality, community characteristics were nearly invariant. In the “grazer-free” (0.8-μm-filtered) treatment, subject only to a relatively low mortality rate (∼17% day(−1)) from viral lysis, bacteria increased markedly in concentration. While the mean bacterial cell volume was invariant, DGGE indicated a shift in BCC and FISH revealed an increase in the proportion of one lineage within the beta proteobacteria. In the grazing-enhanced treatment (5-μm filtrate), grazing mortality was ∼200% and viral lysis resulted in mortality of 30% of daily production. Cell concentrations declined, and grazing-resistant flocs and filaments eventually dominated the biomass, together accounting for >80% of the total bacteria by the end of the experiment. Once again, BCC changed strongly and a significant fraction of the large filaments was detected using a FISH probe targeted to members of the Flectobacillus lineage. Shifts of BCC were also reflected in DGGE patterns and in the increases in the relative importance of both beta proteobacteria and members of the Cytophaga-Flavobacterium cluster, which consistently formed different parts of the bacterial flocs. Viral concentrations and frequencies of infected cells were highly significantly correlated with grazing rates, suggesting that protistan grazing may stimulate viral activity.